Haare hören - Strukturen wissen - Räume agieren Berichte aus dem Interdisziplinären Labor on("i") Bild Wissen Gestaltung off("i") - Bredekamp, Horst; Schäffner, Wolfgang (Einzelveröffentlichungen Kulturwissenschaften, 2015)
What happens when the functional principle of the human ear is translated into the field of nanotechnology, a map depicting epistemological architecture is sketched as a lecture performance, or when researchers from over 25 disciplines critically engage with structures and models? Which new discoveries are brought about through the collaboration between biomorphology and art history, media studies and medicine? And what can the Gestaltung disciplines of design and architecture contribute to this foundational research? This volume gathers together essays from the Cluster of Excellence Image Knowledge Gestaltung, and, through its focus on the these three eponymous keywords, sheds light on the productivity of these diverse research approaches: from methodological transfers between the individual participating disciplines through to the interdisciplinary drafting of new structures of knowledge and research.